2023
DOI: 10.1128/spectrum.03846-22
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Promotes Persistence of Stenotrophomonas maltophilia via Increased Adherence to Depolarized Respiratory Epithelium

Abstract: Despite advances in treatment options for people with CF, complications of bacterial infections remain the greatest driver of morbidity and mortality in this patient population. These infections often involve more than one bacterial pathogen, and our understanding of how interspecies interactions impact disease progression is lacking.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Production of styrene in the human body associates with an aerobic bacterial metabolism of Pseudomonas aeruginosa [32] mostly found in ears, nose, throat, bovine gut, and on skin [45] . Previous studies have been reported an association between Pseudomonas aeruginosa and several conditions, including pneumonia, enteritis, vaginitis, mastitis, and cirrhosis [46–47] . This pathogenic bacterium has the ability to release different microbial VOCs, and toxins leading to cell membranes degrading when the bacterium works together with cytochrome enzyme(CYP) [25,29] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of styrene in the human body associates with an aerobic bacterial metabolism of Pseudomonas aeruginosa [32] mostly found in ears, nose, throat, bovine gut, and on skin [45] . Previous studies have been reported an association between Pseudomonas aeruginosa and several conditions, including pneumonia, enteritis, vaginitis, mastitis, and cirrhosis [46–47] . This pathogenic bacterium has the ability to release different microbial VOCs, and toxins leading to cell membranes degrading when the bacterium works together with cytochrome enzyme(CYP) [25,29] .…”
Section: Resultsmentioning
confidence: 99%
“…[45] Previous studies have been reported an association between Pseudomonas aeruginosa and several conditions, including pneumonia, enteritis, vaginitis, mastitis, and cirrhosis. [46][47] This pathogenic bacterium has the ability to release different microbial VOCs, and toxins leading to cell membranes degrading when the bacterium works together with cytochrome enzyme(CYP). [25,29] In addition, benzene intaking in the human body by inhalation is a substrate for styrene production mostly found in breath and skin as microbial metabolite.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…These two pathogens can form a polymicrobial biofilm in the lungs, interact through quorum-sensing signals and create a favourable environment for each other (47). McDaniel et al (48) found that the presence of P. aeruginosa facilitated S. maltophilia persistence in the lungs during polymicrobial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, LHL-1 and LHL-37 both exhibited a moderate ability to form biofilms and virulence profiles were also identical. The contained virulence factors were primarily contributed to the biofilm formation and colonization in infection [ 31 ]. Infection caused by P. aeruginosa with certain biofilm capacity poses a threat to clinical treatment.…”
Section: Discussionmentioning
confidence: 99%